Structural and mechanical properties study of thermoplastic starch reinforced with rice husk biochar: article - Mohd Zamzuri, Farah Ayunie; Sauid, Suhaila (2017)
The morphological and mechanical properties study of thermoplastic starch (TPS) film from Tacca leontopetaloides reinforced with rice husk biochar (RHB) was investigated in this study. T. leotopetaloides was chosen as a good source of starch since it is cheap, readily available, abundance in nature and it is not a staple food in Malaysia. Using T. leontopetaloides starch as the main ingredient for TPS is a new idea to produce biodegradable compound in order to control environmental problem by reducing the agricultural waste disposal problem. The TPS/RHB biocomposites were developed from casting method. RHB infiltration into TPS was performed by rolling them with roll mill. The improvement of the properties of TPS with biochar has significantly increased the tensile strength and elongation at break properties of TPS. X-ray Diffraction analysis showed that the TPS/RHB blends displayed crystallinity characteristics at peak of 22°. Based on the results potrayed by the analyses, it was clearly proven that the incorporation of RHB into TPS has brought a great improvement of mechanical properties of TPS.